Inter-laminar shear stress in hybrid CFRP/austenitic steel (Fracture and Structural Integrity, 2014)
Bolted joints are the most common solution for joining composite components in aerospace structures. Critical structures such as wing to fuselage joints, or flight control surface fittings use bolted joining techniques. Recent research concluded that higher bearing strengths in composite bolted joints can be achieved by a CFRP/ Titanium hybrid lay-up in the vicinity of the bolted joint. The high costs of titanium motivate a similar research with the more cost competitive austenitic steel. An experimental program was performed in order to compare the apparent inter-laminar shear stress (ILSS) of a CFRP reference beam with the ILSS of hybrid CFRP/Steel beams utilizing different surface treatments in the metallic ply. The apparent ILSS was determined by short beam test, a three-point bending test. Finite element models using cohesive elements in the CFRP/Steel interface were built to simulate the short beam test in the reference beam and in the highest interlaminar shear stress hybrid beam. The main parameters for a FEM simulation of inter laminar shear are the cohesive elements damage model and appropriate value for the critical energy release rate. The results show that hybrid CFRP/Steel have a maximum ILSS very similar to the ILSS of the reference beam. Hybrid CFRP/Steel is a competitive solution when compared with the reference beam ILSS. FEM models were able to predict the maximum ILSS in each type of beam.
Keywords: Experimental techniques